Factors Causing the Decline in Voter Participation in the 2024 Bantul Regency Election - Nessa Rizky Indriyani; Ridho Al-Hamdi (Universitas Medan Area, 2025)
This article aims to discover the factors causing the decline in voter participation in the 2024 simultaneous regional elections in the Bantul district. The problem in this study is due to a decrease in the voter participation rate in the 2024 Simultaneous Regional Head Election (Pilkada) in Bantul Regency, where the participation rate in 2020 is 80.32% and in 2024 at 75.96%. In this case, a theoretical reference from Ramlan Surbakti about Political Participation is used. Using a qualitative method with a case study approach in the 2024 Bantul regent and deputy regent elections. With data collection techniques through interviews and documentation. Based on the results of the research. This shows that most people have a negative view of the Government's performance and do not have reasonable expectations of all candidates; this is also due to the lack of direct socialization to the public from each candidate to maximize the existing campaign period. However, the following two factors also affect the decline in voter participation: the situation and political instability. One factor that does not affect is social and economic status.